BILINGUAL PEDAGOGY: DILEMMAS AND CHALLENGES IN TEACHER TRAINING - Mosca Giroto, Claudia Regina [UNESP]; Munhoz Cicilino, Joice Emanuele [UNESP]; Poker, Rosimar Bortolini [UNESP] (Unesp-faculdade Ciencias & Letras, 2018)
This theoretical work implied to discuss and problematize the existing inconsistencies between the conceptions about bilingual education that guide educational actions with deaf students and the proposals of teacher training to consolidate such actions in the inclusive education context. The systematization of bilingual education as provided by national legislation, under the auspices of current inclusive educational policy, raises dilemmas insofar as it seems to demarcate the mismatch between public policies and / or applicable legal provisions, the proposals for initial teacher training and the reality educational. The idea that the presence of the Brazilian Language of Signs (LIBRAS) in the deaf student learning environments (classes and schools) and in pedagogy courses would be sufficient to implement the bilingual approach is refuted It examines the place of LIBRAS reflecting on its role in an effectively bilingual and inclusive proposal for deaf students.
Keywords: Education of the deaf; Bilingualism; Teacher training for the deaf; Brazilian Language of Signs (LIBRAS)